Green Synthesis of Gold Nanoparticles with Curcumin or Açai in the Tissue Repair of Palatal Wounds - Anand Thirupathi; Morgana Francisco Machado Guzzatti; Maria Eduarda Anastácio Borges Corrêa; Ligia Milanez Venturini; Laura de Roch Casagrande; Igor Ramos Lima; Camila Da Costa; Ellen De Pieri; Lariani Tamires Witt Tietbohl; Paulo Emilio Feuser; Ricardo Andrez Machado-de-Ávila; Yaodong Gu; et al. (Antioxidants, 2023)
This study aimed to evaluate and compare the effects of treatment with gold nanoparticles (GNPs) reduced with Curcumin (Curcuma longa L.) or Açai (Euterpe oleracea) to a standard commercial treatment of the pharmacological type (Omcilon®) and an electrophysical agent (photobiomodulation) in the palatal wounds of rats. As for the in vitro assay, a cell viability test was performed to assess the toxicity of the synthesized nanoparticles. In vivo assay: 60 Wistar rats were divided into five groups (n = 12): I. Palatal Wound (PW); II. PW + Photobiomodulation (PBM); III. PW + Omcilon®; IV. PW + GNPs-Cur (0.025 mg/mL); V. PW + GNPs-Açai (0.025 mg/mL). Animals were first anesthetized, and circular lesions in the palatine mucosa were induced using a 4 mm-diameter punch. The first treatment session started 24 h after the injury and occurred daily for 5 days. The animals were euthanized, and the palatal mucosa tissue was removed for histological, biochemical, and molecular analysis. GNPs-Açai were able to significantly reduce pro-inflammatory cytokines and increase anti-inflammatory ones, reduce oxidant markers, and reduce inflammatory infiltrate while increasing the collagen area and contraction rate of the wound, along with an improved visual qualification. The present study demonstrated that the proposed therapies of GNPs synthesized greenly, thus associating their effects with those of plants, favor the tissue repair process in palatal wounds.